Evaluate the diagnosis of neonatal sepsis by measuring interleukins: A systematic review - Hassan Boskabadi; Maryam Zakerihamidi (Pediatrics and Neonatology)
Neonatal sepsis is a dangerous and common disease among infants which is associated with high morbidity and mortality. Interleukins may be helpful for diagnosis of neonatal sepsis. Therefore, this study is conducted to investigate the role of interleukins in the diagnosis of neonatal sepsis. In this study, databases including PubMed, Cochrane Library, ISI and Google Scholar were searched up to 2016. Keywords were: Sepsis, neonatal, interleukins, prediction and diagnosis. Study inclusion criteria were: Articles about the relationship between the diagnosis of neonatal sepsis and interleukins; studies on babies; English and Persian articles and enough information from test results. Articles that had focused on adult sepsis or had used other markers except ILs or just their abstracts were available were excluded from the study. Of 100 searched studies, eventually, 16 articles were considered including 12 prospective studies, 3 cross-sectional studies and 1 retrospective study. IL6 has been studied more than other interleukins (50% of articles). ILs 6, 8 and 10 are among the initial markers of neonatal sepsis diagnosis. IL6 above 68 pg/ml had 85% sensitivity and 80% specificity, IL8 above 269.51 pg/ml had 80% sensitivity and 50% specificity, IL10 above 27 pg/ml had 60% sensitivity and 87% specificity and combined interleukins above 186.83 pg/ml had 75.63% sensitivity and 71.49% specificity in sepsis diagnosis. Interleukins can be helpful in the diagnosis of neonatal sepsis based on the results of this study. IL6 had the most sensitivity and IL10 had the most specificity for diagnosis of sepsis. Key Words: diagnosis, interleukins, neonatal, sepsis